Pathogen reductions associated with traditional processing of landjäger. (March 2017) - Rivera-Reyes, Minerva; Campbell, Jonathan A.; Cutter, Catherine N.
Abstract: To determine if traditional processing would reduce Escherichia coli O157:H7 (EC), Listeria monocytogenes (LM), and Salmonella spp. (S) in landjäger, beef and pork trim (95% lean) and pork fat was experimentally-inoculated to obtain a pathogen population of ca. 8 log10 CFU/g. The trim was spray-treated with 4.5% lactic acid (30 min, 25 °C), ground, mixed with seasonings, and a starter culture added. Sausages were stuffed, pressed, fermented (to pH 4.8), cold smoked, and dried to a water activity of 0.88. Sausages were vacuum packaged, stored (20 days, ca. 23 °C), and evaluated for microbial populations, pH, and water activity. Lactic acid treatment of beef trim reduced EC, S, and LM 0.23, 0.42, and 0.22 log10 CFU/g, respectively. Subsequent fermentation and drying reduced EC, LM, and S 3.94, 4.11, and 4.29 log10 CFU/g respectively. Average log reductions of 7.83, 6.19, and 7.21 log10 CFU/g were observed for EC, LM and S, respectively, for the duration of the study. This study demonstrates that traditional processing of landjäger may result in a ca. 5 log reduction of foodborne pathogens. Highlights: Landjäger, a dry fermented sausage, was evaluated for safety via a challenge study. Beef and pork trim was experimentally inoculated with foodborne pathogens. Multiple hurdles achieved >5 log reduction in pathogens in the final product. This study demonstrates that processing of landjäger can result in a safe product.